Managing increasing environmental risks through agro-biodiversity and agri-environmental policies - Stefan Baumgärtner; Martin F. Quaas (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
Agro-biodiversity can provide natural insurance to risk-averse farmers by reducing the variance of crop yield, and to society at large by reducing the uncertainty in the provision of public-good ecosystem services such as e.g. CO2 storage. We analyze the choice of agro-biodiversity by risk-averse farmers who have access to financial insurance, and study the implications for agri-environmental policy design when on-farm agro-biodiversity generates a positive risk externality. While increasing environmental risk leads private farmers to increase their level of on-farm agro-biodiversity, the level of agro-biodiversity in the laissez-faire equilibrium remains inefficiently low. We show how either one of two agri-environmental policy instruments can cure this risk-related market failure: an ex-ante Pigouvian subsidy on on-farm agro-biodiversity and an ex-post compensation payment for the actual provision of public environmental benefits. In the absence of regulation, welfare may increase rather than decrease with increasing environmental risk, if the agroecosystems is characterized by a high natural insurance function, low costs and large external benefits of agro-biodiversity.
Keywords: Q1; Q57; H23; D62; 330; Agrarsubvention; Biodiversität; Umweltschutz; Landwirtschaft; Risikoaversion; Wohlfahrtseffekt; Theorie